L’album Panini, un outil de l’enseignant géographe ? - Xavier Leroux (EchoGéo)
This article proposes to examine the relevance of the Panini's album Collectionne Tourcoing to develop one's cultural and spatial knowledge. As a first for this editor, this media invites children to collect 50 stickers representing the town's iconic and heritage sites. A survey to identify places of the stickers set in 4 primary school classes (children from 9 to 11 years old) in the town will test the concept's validity in accompanying the teaching of geography.